2018
DOI: 10.1021/acs.jpcc.8b09606
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Occupied and Unoccupied Hybrid Bands at Interfaces between Metals and Organic Donors/Acceptors

Abstract: Efficient charge transport in organic semiconductors and at their interfaces with electrodes is crucial for the performance of organic moleculebased electronic devices. Band formation fosters effective transport properties and can be found in organic single crystals of large π-stacking aromatic molecules. However, at molecule/metal interfaces, hybrid band formation and band dispersion is a rarely observed phenomenon. Using angle-resolved twophoton photoemission supported by density functional theory calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 59 publications
(100 reference statements)
3
20
0
Order By: Relevance
“…To study the role of adatoms, we chose F4TCNQ on Au(111), since multiple independent studies have found that it readily and reproducibly forms well-ordered structures containing adatoms as part of the adlayer. 35 , 44 , 46 , 47 The surface structure consists of only one F4TCNQ molecule and one adatom per unit cell, which reduces the computational effort and facilitates the analysis of this system (compared to larger unit cells). The strong interactions between the adsorbate and substrate lifts the herringbone reconstruction of Au(111), and the F4TCNQ molecule-Au-adatom network is arranged in a Au(111) surface supercell, as shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the role of adatoms, we chose F4TCNQ on Au(111), since multiple independent studies have found that it readily and reproducibly forms well-ordered structures containing adatoms as part of the adlayer. 35 , 44 , 46 , 47 The surface structure consists of only one F4TCNQ molecule and one adatom per unit cell, which reduces the computational effort and facilitates the analysis of this system (compared to larger unit cells). The strong interactions between the adsorbate and substrate lifts the herringbone reconstruction of Au(111), and the F4TCNQ molecule-Au-adatom network is arranged in a Au(111) surface supercell, as shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we used the “tight” defaults, which were shown to yield converged results in a previous work. 44 Going beyond these settings, we furthermore increased the onset of the basis set cutoff potential from the default of 4 to 6 Å in order to obtain adsorption energies converged within 1 meV (see Supporting Information ).…”
Section: Methodsmentioning
confidence: 99%
“…P4O exhibits a similar chemisorptive behavior on Cu(111), but physisorbs on Au(111) 73,78 . In contrast, F 4 TCNQ chemisorbs on virtually all clean metal surfaces 58,66,329, [439][440][441][442][443][444][445] showing a qualitatively similar behavior. These systems shall hence be discussed as model systems for strongly coupled organic-metal interfaces.…”
Section: Strongly Interacting Systemsmentioning
confidence: 95%
“…Hybridization is a necessary prerequisite for interfacial band formation which can be identified via dispersing states in angle-resolved photoemission experiments. Interfacial band formation has been shown in the case of strong electron acceptors (tetrafluoro-tetracyanoquinodimethane (F 4 TCNQ)/Au(111), 39,40 3,4,9,10-perylene-tetracarboxylic-dianhydride (PTCDA)/ Ag(110) 41 and 1,4,5,8-naphthalenetetracarboxylicdi-anhydride (NTCDA)/Ag(111) 41,42 ) and a donor (tetrathiafulvalene (TTF)/Au(111) 40 ) adsorbed on noble metal surfaces. Recently, we demonstrated interfacial band formation for a N-heteropolycyclic molecule, a 1,3,8,10tetraazaperopyrene derivative (TAPP-CF 3 , see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This state has an effective mass of m * = -0.86 ± 0.24 m e .While hybridization between molecular and metal states occurs in many organic/metal systems, experimental evidence for interfacial band formation via dispersing electronic states is rarely observed. Only for strong electron acceptors (F4TCNQ/Au(111),39,40 PTCDA/ Ag(110),41 NTCDA/Ag(110)42 ) or a donor (TTF/Au(111)40 ), dispersing interface bands have been proposed. In all cases a charge transfer between molecular states and the surface state of the metallic substrate appears (Fermi-level pinning).…”
mentioning
confidence: 99%